A Jack of All Trades: The Role of Pneumococcal Surface Protein A in the Pathogenesis of Streptococcus pneumoniae - Lane, Jessica R.; Tata, Muralidhar; Briles, David E.; Orihuela, Carlos J. (Frontiers in Cellular and Infection Microbiology, 2022)
Streptococcus pneumoniae (Spn), or the pneumococcus, is a Gram-positive bacterium that colonizes the upper airway. Spn is an opportunistic pathogen capable of life-threatening disease should it become established in the lungs, gain access to the bloodstream, or disseminate to vital organs including the central nervous system. Spn is encapsulated, allowing it to avoid phagocytosis, and current preventative measures against infection include polyvalent vaccines composed of capsular polysaccharide corresponding to its most prevalent serotypes. The pneumococcus also has a plethora of surface components that allow the bacteria to adhere to host cells, facilitate the evasion of the immune system, and obtain vital nutrients; one family of these are the choline-binding proteins (CBPs). Pneumococcal surface protein A (PspA) is one of the most abundant CBPs and confers protection against the host by inhibiting recognition by C-reactive protein and neutralizing the antimicrobial peptide lactoferricin. Recently our group has identified two new roles for PspA: binding to dying host cells via host-cell bound glyceraldehyde 3-phosphate dehydrogenase and co-opting of host lactate dehydrogenase to enhance lactate availability. These properties have been shown to influence Spn localization and enhance virulence in the lower airway, respectively. Herein, we review the impact of CBPs, and in particular PspA, on pneumococcal pathogenesis. We discuss the potential and limitations of using PspA as a conserved vaccine antigen in a conjugate vaccine formulation. PspA is a vital component of the pneumococcal virulence arsenal – therefore, understanding the molecular aspects of this protein is essential in understanding pneumococcal pathogenesis and utilizing PspA as a target for treating or preventing pneumococcal pneumonia.